Knowledge Sharing Behavior Factors of Public Sector Employees in Jambi, Indonesia - Ahmad Firdaus; Eeng Ahman (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2020)
The purpose of this research is to evaluate the individual, organizational and technological factors that influence knowledge sharing behavior among public sector employees in Jambi City. This is a survey and explanatory research with questionnaires used to obtain data from 86 employees in Jambi's public sector and analyzed using factor analysis. The results showed that individual, organizational, and technological factors, such as awareness and altruism, organizational rewards, and IT application usage, respectively, have a significant effect on knowledge sharing. This is opposed to self-efficacy and top management support.